Hardiness as a Factor of Intercultural Adaptation of Foreign Students from Different Regions - O A Kadilnikova (Peoples' Friendship University of Russia (RUDN University), 2011)
The correlation between the parameters of hardiness and the intercultural adaptation of foreign students of PFUR from Africa and Haiti is analyzed in the article. The sample included 52 students: 25 French-speaking students from Haiti and 27 French-speaking students from Africa.